A REVIEW OF STUDY AND ANALYSIS OF STRENGTH PROPERTIES OF CALCINED KAOLIN AND SILICA FUME WITH COMPOSITION - Elahi, Kamar; Gupta, Harsh (International Journal of Engineering Technologies and Management Research, 2021)
Cement is used in any construction and can be hydraulic or non-hydraulic, which directly depends on the cement’s ability to use the presence of water. When high purity quartz is reduced to silicon at temperatures of up to 2000 ° C, SiO2 vapors are formed, which are oxidized and condensed in the low temperature zone into tiny particles made of non-crystalline silica.